Evolution of the Beach–Dune Systems in Mediterranean Andalusia (Spain) Using Two Different Proxies - Rosa Molina; Giorgio Anfuso; Belén González-Aguilar; Giorgio Manno; J. Andrew G. Cooper (Land, 2024)
Coastal environments are complex systems that are influenced by a combination of natural processes and human activities. Scientific interest in the effects of coastal erosion/accretion and climatic change-related processes has greatly increased in recent decades due to the growing human development along coastal areas. This paper investigates the state and evolution of beach–dune systems for the 1977–2001 and 2001–2019 periods of the Mediterranean coast of Andalusia (Spain) using two different proxies: the dune toe line, which was used to track foredunes evolution, and the high-water line, which was used to assess shoreline evolution. Results showed a general erosional behavior of the studied beach–dune systems and identified cases where the main trend was altered through human interventions. During the 1977–2001 period, foredunes essentially showed erosion (54%), accretion (24%), and stability (22%) and shorelines showed accretion (40%) and erosion and stability (34% each). During the 2001–2019 period, foredunes essentially showed erosion (42%), stability (30%), and accretion (28%), and shorelines showed erosion (40%), accretion (34%), and stability (26%). Combining the evolution classes of each proxy (dune toe/shoreline) allows the behavior of both shoreline proxies to be assessed together and provides insights additional to those derived from the use of a single proxy. In this regard, Erosion/erosion (EE) and Accretion/accretion (AA) were the most frequent behaviors in the first and second periods. The results obtained provide additional insights on the nature and drivers of coastal change that aid local coastal managers and administrations in understanding erosion processes. The method can be applied to other areas around the world where a similar database is available.